Re-Evaluation Curriculum and Implementation: Case Study in MTsS PTP-VI Berangir - Pohan, Muhammad Munawir (International Journal for Educational and Vocational Studies, 2020)
This study aims to evaluation of implementation the 2013 Curriculum in MTsS PTP-VI Berangir which includes (1) readiness for implementation; (2) learning process and learning evaluation, (3) results of implementation; and (4) level of successful implementation. The method used in this study is the method of evaluating the Countenan Stake model which divides the curriculum components in the observation matrix and the consideration matrix including the antecedent, process (transaction), and results (outcomes) stages. The study was conducted at MTsS PTP-VI Berangir, North Labuhanbatu Regency, North Sumatra Province which is a private school. The results showed that the preliminary stage or readiness for implementation included the readiness of teachers, books, infrastructure, and lesson plans very well (90%), the stage of the process which included learning activities and learning evaluation was very good (97%), and the results of implementation which included responses students and learning outcomes are also very good (95%). The implementation of the 2013 Curriculum in MTsS PTP-VI Berangir can run very well with the support of meeting national education standards and teachers who have good motivation, creativity and performance.